2019
DOI: 10.1002/cam4.2787
|View full text |Cite
|
Sign up to set email alerts
|

Loss of skeletal muscle index and survival in patients with metastatic colorectal cancer: Secondary analysis of the phase 3 CAIRO3 trial

Abstract: Background: Low skeletal muscle index (SMI) in metastatic colorectal cancer (mCRC) patients is associated with poor outcomes. The prognostic impact of SMI changes during consecutive palliative systemic treatments is unknown. Methods: This is a retrospective analysis of the phase 3 CAIRO3 study. The CAIRO3 study randomized 557 patients between maintenance capecitabine + bevacizumab (CAP-B) or observation, after six cycles capecitabine + oxaliplatin + bevacizumab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
1
28
2
Order By: Relevance
“…Although previous studies have shown that loss of SMM in patients who received cancer treatment [14][15][16]31] had significant prognostic impact on survival, in this study, a loss in SMM showed no prognostic impact for OS nor DFS. This difference may be explained by the heterogeneity in the definition of muscle mass changes, the timing of the follow-up imaging, and the type and stage of cancer and its type of treatment.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Although previous studies have shown that loss of SMM in patients who received cancer treatment [14][15][16]31] had significant prognostic impact on survival, in this study, a loss in SMM showed no prognostic impact for OS nor DFS. This difference may be explained by the heterogeneity in the definition of muscle mass changes, the timing of the follow-up imaging, and the type and stage of cancer and its type of treatment.…”
Section: Discussioncontrasting
confidence: 76%
“…The median time between follow-up imaging and pre-CRT imaging in our study was 6 months (range 5-9). In previous studies conducted in non-HNC cancer patients in which loss of SMM showed to have prognostic value, this interval ranged between 9-27 months [27] and 9-18 weeks [15]. In addition to the difference in time interval between this study and previous studies, there was also a difference in the investigated study population.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…10 In the CAIRO-3 trial investigating first-line bevacizumab and oxaliplatin-including regimens for metastatic CRC, a decrease in SMI during the treatment was related to early disease progression and reduced survival. 11 Even in later-line chemotherapy, skeletal muscle loss during regorafenib or trifluridine/ tipiracil was associated with OS in two recent retrospective studies, both of which also showed that only patients who received regorafenib showed a significant reduction in skeletal muscle. 12,13 Regarding resectable stage IV CRC, van Vledder et al reported a correlation between preoperative sarcopenic status and poor RFS or OS after hepatectomy for colorectal liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, several longitudinal studies also found that a reduction in skeletal muscle mass during systemic therapy is related to early disease progression or poor survival in metastatic CRC patients. [9][10][11][12][13] In the non-metastatic setting, a low skeletal muscle index (SMI) or psoas muscle index (PMI) at lumbar levels before surgery led to a poor survival in CRC patients. 14,15 A population-based study revealed that longitudinal decreases in muscle mass and density during the first 1-2 years after diagnosis are related to overall and cancer-specific mortalities in stage I-III CRC.…”
Section: Introductionmentioning
confidence: 99%